Does Personality Influence Pre-service English Teachers' Performance?: A Gender-Based Study in the Yemeni Context (Journal of Education and Development, 2019)
This study mainly investigated whether there is any correlation between the Big Five Personality Traits of pre-service teachers and their performance in Practicums I&II, and attempted to identify the extent to which the personality traits affect pre-service teachers' performance. To fulfill the purpose of the study, a sample of 110 fourth-year student-teachers; 86 females & 24 male, of the English Department, in the Faculty of Education at Hodeidah University, was selected . They enrolled in the four-year B.Ed. course. The Big Five Inventory (BFI) originally developed by John & Srivastava (1999) with little modification was distributed among the selected subjects. This inventory comprised of forty-four statements about the big five personality traits that are Extraversion, Agreeableness, Conscientiousness, Neuroticism and Openness. Collected data was analyzed by using simple descriptive and inferential statistical techniques such as mean, Pearson correlation, t-test and f-test. It was found that there is a relationship between the pre-service teachers' performance in Practicums I&II and their personality traits so pre-service teachers' personality DO influence their performance of teaching English. Also, pre-service teachers' personality traits of Extraversion, Agreeableness, and Conscientiousness are nearly same, so no significant difference found among male and females on these three traits. However, significant difference exists among the females and males on the trait of Neuroticism as female student-teacher score higher than males on this trait. Moreover, both male and female pre-service teachers have quite good level of Extraversion and Agreeableness, and similar reasonable level of Conscientiousness and Neuroticism but their level of Openness is a very low. It is recommended that Teacher Personality Development should be a part of teacher education programs and suggest some strategies for development of pre-service teachers’ personality.